2016
DOI: 10.3233/jad-150962
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer’s Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies

Abstract: Abstract. Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 39 publications
8
102
0
Order By: Relevance
“…In addition, Barthelemy et al . (32) also observed a twenty fold difference when comparing their ELISA and SRM assays, illustrating the difference we could expect when comparing ELISA and SRM on the same region of the protein. When comparing the absolute concentration for tau, measured with SRM, our current values are consistent with previous studies (19), and the concentrations in both cases are in the nanogram per milliliter range.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, Barthelemy et al . (32) also observed a twenty fold difference when comparing their ELISA and SRM assays, illustrating the difference we could expect when comparing ELISA and SRM on the same region of the protein. When comparing the absolute concentration for tau, measured with SRM, our current values are consistent with previous studies (19), and the concentrations in both cases are in the nanogram per milliliter range.…”
Section: Discussionmentioning
confidence: 90%
“…The disappointing results from amyloid beta treatment studies has caused a shift in focus to the treatment of tau in AD. More recently, CSF biomarker studies have indicated that tau is superior to amyloid beta markers in following the progression of cognitive deficits in AD and other tauopathies [46, 47]. Furthermore, a newly developed PET technique to track changes in tau deposition in living patients with AD also shows that tau deposition more closely tracked dementia status and was a better indicator of cognitive deficits, thus indicating that treatments targeting tau could provide a superior alternative to amyloid beta therapies [45].…”
Section: Treatments To Reduce Pathogenic Tau Isoforms In Ad Tbi and Ctementioning
confidence: 99%
“…Hence, in those less common conditions, tau antibodies may need to work intracellularly to be effective. In this context, it is also important to note that recent mass spectroscopy studies show that most of CSF tau consists of tau fragments with ragged N- and C-termini that approximately consist of Tau150–250 [61,62]. Although there should be less tau degradation in interstitial fluid, a gradient of such cleavage likely exists in biological fluids that should influence antibody target engagement and clearance of pathological tau.…”
Section: How Does It Work?mentioning
confidence: 99%